KLASIFIKASI ANGIN BERDASARKAN KECEPATAN ANGIN DENGAN SKALA BEAFORT PADA PERAIRAN CILACAP - Lusiani (Saintara: Jurnal Ilmiah Ilmu-Ilmu Maritim, 2017)
There has been an analysis of wind classification in Cilacap waters. The analysis was performed using Beafort scale. The analysis is done based on data obtained that is related to wind speed data. Based on the percentage of wind velocities observed at one year in two water points in Cilacap showed that the winds move at the highest speed at the second point (109.260000 E and 7.950000 S) of 40.1% with values over 22 knots, but did not show any significant difference with wind speed at the first point if classified by beafort scale. Based on the results of the analysis that has been done before, it can be seen that the value 11.303 m / s can be classified including scale 7 with description of strong wind gusts. The conclusion obtained is wind classification based on wind velocity by using beafort scale in cilacap waters that is including scale 7 with description of strong wind gusts.